Estudio de prefactibilidad para la Instalación de un m-commerce modelo dropshipping por medio de una aplicación móvil con tecnología de realidad aumentada - Angulo Montes, Luis Enrique (2020)
Nowadays, companies are migrating into a virtual sales platform due to the several benefits that it offers. Online shopping and sales generate savings in different costs that the seller reflects in the price. Also, this benefit makes the final client decide to buy online rather than in a regular shop. However, there is an issue when buying online, people cannot try articles before buying them generating product returns, waste of time and customers’ dissatisfaction. According to the detailed problem, the team intends to innovate when selling the products online by using an augmented reality app and smart dummies that combined assure the client that the clothes they are buying have.